THE EFFECT OF COMPETENCE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE IN THE PROTOCOL AND COMMUNICATION DEPARTMENT OF THE SOUTH LAMPUNG REGENCY LEADERSHIP - Usman, Ahmad; Ahiruddin, Ahiruddin (University of Sang Bumi Ruwa Jurai, 2025)
Competence plays an important role in determining the quality of an employee's work and their understanding of their field of work. A professional must have academic qualifications and abilities that are appropriate to their field of work in order to make an optimal contribution to the organization. Competence is also a measure of individual behavior related to excellent performance at work. In the face of increasingly fierce competition, organizations need quality human resources as a key factor for success. Human resources with high competencies will support the smooth implementation of tasks and the achievement of organizational goals. Conversely, if the quality of human resources is low, the overall performance of the organization will decline. This study aims to examine the influence of competencies and career development on employee performance in the Protocol and Communication Division of the South Lampung Regency. Involving 53 respondents and using quantitative analysis methods through the SPSS program, the results showed that competence had a positive effect on performance with a contribution of 69.3%, while career development had a positive effect of 74.9%. Simultaneously, both variables had a positive effect on employee performance of 80.7%, while the remaining 19.3% was influenced by other factors outside the scope of this study.